Justiça restaurativa e crimes ambientais de menor potencial ofensivo. - Ocampos, Juliana Buck Gianini (2016)
As the traditional paradigm of penal cases handling faces a crippling crisis, thinkers have begun to focus their academic attention towards the establishment and standardization of fresh solutions for criminal accountability against offenders. The Restorative Justice has been proposed by national jurisprudence as a sanction alternative among several others. It promotes opening of conciliatory dialog between both parties involved in a penal conflict, in order to spread creative restitution of damage inflicted upon the environment, as well as socially reintegrate misdemeanor offenders. This new proposal of crime management states that our national judiciary system offers legal support to restorative, consensual justice, and the Law of Crimes against the Environment allows such solution. It is rooted in the conditional suspension of proceedings and it was judicially installed by the Law of Special Criminal and Civil Courts (Federal Law 9009/1995) which properly regulates the acceptance of mutually consensual deals signed on a restorative agreement. As for the violations against the environment, the proposed legitimate party to work as proxy for the community is the Attorney General who is in charge to either probate or not all agreements signed on conciliatory hearings regarding misdemeanors against the environment at Justice Centers for Conflict and Citizenship Resolutions (Federal Laws 9605/98, 9099/1995 and 10259/2011). That procedure enables implementation of restorative justice as well as alternative dispute resolutions in environment-related criminal cases which offend several collective legal interests. Whenever conflicts are analyzed by the Attorney General under the guidelines of traditional retributive penal law, common interest should prevail.